Does Political Competition Lessen Ethnic Discrimination? Evidence from Sri Lanka - Sharif, Iffath A. (2012)
The impact of political competition on ethnic discrimination remains largely unexplored. To address this gap, this paper explores the relationship between the level of political competition and the probability of receiving government transfers among ethnic minorities in Sri Lanka in the run up to the national elections of 2000. The paper shows that making politicians dependent on the votes of members of ethnic groups other their own can encourage moderation in discriminatory practices towards ethnic minorities. Specifically we find that political competition positively influenced the distribution of government food stamps among Sri Lankan Tamils, who otherwise are less likely to receive food stamps relative to the Sinhalese majority. The negative impact of political competition on discrimination is higher when minorities form part of swing constituencies than when they form part of the base support for political parties. Lessons learnt here suggest that having built-in incentives in the design of the electoral process for intergroup bargaining and cooperation in countries with ethnically heterogeneous societies can be an effective restraint on ethnic discrimination. This is consistent with other research that considers political institutions to be a key lever for making ethnically divided societies more inclusive.